Risk Assessment and Management in Real Estate Project - Srinivas, K. (AMC Indian Journal of Civil Engineering, 2020)
The construction industry in general and the real estate industry in particular have undergone tremendous changes over the past few years. It is an industry driven primarily by private investors and the presence of securitised real estate has increased considerably. The vulnerability of real estate to plethora of risks causes more exposures than those that can be insured and this cannot be understated. To be successful in this environment, where the collective performance bar is being raised significantly, the real estate industry needs to gear up to address the risks by deploying effective risk management techniques by way of operational sophistication. This paper deals with risks in real estate project and measures to be taken to mitigate the same.